Pan speaks – Mythologising Non-human Voices in Neil Gaiman's Stardust and Guillermo Del Toro's Pan's Labyrinth. Issue 3 (3rd July 2019) - Potter, Mary-Anne
Summary: Narrative myth tellings have the magical capacity to give voice to the non-human and to initiate dialogue between forces and figures previously assumed to be binary opposites. These well-established binaries draw on the multi-dimensional experience of the "collective unconscious" (Jung 1964: 153), and so mythological readings of human/non-human relationships are informed by an awareness of this. Such readings require an interdisciplinary approach. It is through this interdisciplinary engagement that the complexities of narrative myth tellings are unravelled, and the tenuous human mastery over an Othered natural world - whether real or fantastical - is revealed. The relegation of Nature to silent setting is being challenged by a growing ecocritical need to establish and acknowledge Nature's counter-voice - to resurrect Pan who, according to writers such as D.H. Lawrence, had been killed by ideology and human ambition. Hearing him speak once more in fantasy narratives such as Neil Gaiman's Stardust (1999) and Guilermo del Toro's Pan's Labyrinth (2006), represents a significant resurrection of the mythological influence of Nature over Culture. Drawing on various mythological and ecocritical theorists, this article attempts to determine the agency with which the non-human voice, as represented by Pan, speaks in these fantasy narratives, and how this, in turn, informs anthropocentric views regarding natural and cultural appropriation.